2023
DOI: 10.22452/ijie.vol15no2.3
|View full text |Cite
|
Sign up to set email alerts
|

Skills Acquisition and Employability Among Arts and Social Sciences Interns in a Malaysian Public University

Abstract: Many Malaysian employers feel that university curricula inadequately prepare graduates for the realities of the job market. The present study attempts to rank skills acquisition among interns at a Malaysian public university and identify the gaps through skills gap and radar analyses. Respondents comprised students from an Arts and Social Sciences faculty in a Malaysian public university who had undergone internship as well as the employers who conducted trainings for them. Using a simple random sampling metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
(38 reference statements)
1
3
1
Order By: Relevance
“…This result differs from previous research who found that females performed better than their male counterparts in terms of the teaching skills acquired during internship (Adu-Marfo et al, 2024;Ahiatrogah, 2017). The other study also observed a small difference in how male and female interns assessed their skill development (Ang, 2015;Monogaran & Subramaniam, 2023). Nevertheless, this study underscores the significance of examining the teacher interns' capabilities rather than forming conclusions based on gender stereotypes when evaluating their learned abilities and inherent characteristics.…”
Section: Discussioncontrasting
confidence: 99%
“…This result differs from previous research who found that females performed better than their male counterparts in terms of the teaching skills acquired during internship (Adu-Marfo et al, 2024;Ahiatrogah, 2017). The other study also observed a small difference in how male and female interns assessed their skill development (Ang, 2015;Monogaran & Subramaniam, 2023). Nevertheless, this study underscores the significance of examining the teacher interns' capabilities rather than forming conclusions based on gender stereotypes when evaluating their learned abilities and inherent characteristics.…”
Section: Discussioncontrasting
confidence: 99%
“…And now, using the platforms as [...] to this day." The result confirmed the result of a study by Monogaran and Subramaniam (2023) that finds ICT skills as one of the important skills for an internship as perceived by the students.…”
Section: Ict Skillssupporting
confidence: 87%
“…Hence, as students transition from an academic setting to the practical realm of internship, their perception of the necessary skills plays an important role in shaping their confidence and overall experience. Monogaran and Subramaniam (2023) conducted a study on -Skills Acquisition and Employability Among Arts and Social Sciences Interns in a Malaysian Public University". The study was done to investigate interns' employability skills from their perspective and determine the necessary skills sought by their employers.…”
Section: Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, international internships provide students with unique networking opportunities and exposure to different business practices and work cultures, significantly enhancing their future career prospects (Monogaran & Subramaniam, 2023). By immersing themselves in international work environments, students gain firsthand experience in navigating diverse professional settings, fostering adaptability and intercultural competence.…”
Section: Opportunities Arising From Participation In International On...mentioning
confidence: 99%